New Biotechnological Tools for the Genetic Improvement of Major Woody Fruit Species - Limera, Cecilia; Sabbadini, Silvia; Sweet, Jeremy B.; Mezzetti, Bruno (Frontiers in Plant Science, 2017)
The improvement of woody fruit species by traditional plant breeding techniques has several limitations mainly caused by their high degree of heterozygosity, the length of their juvenile phase and auto-incompatibility. The development of new biotechnological tools (NBTs), such as RNA interference (RNAi), trans-grafting, cisgenesis/intragenesis and genome editing tools, like zinc-finger and CRISPR/Cas9, has introduced the possibility of more precise and faster genetic modifications of plants. This aspect is of particular importance for the introduction or modification of specific traits in woody fruit species while maintaining unchanged the general characteristics of a selected cultivar. Moreover, some of these new tools give the possibility to obtain transgene-free modified fruit tree genomes, which should increase consumer’s acceptance. Over the decades biotechnological tools have undergone rapid development and there is a continuous addition of new and valuable techniques for plant breeders. This makes it possible to create desirable woody fruit varieties in a fast and more efficient way to meet the demand for sustainable agricultural productivity. Although NBTs have a common goal i.e. precise, fast and efficient crop improvement, individually they are markedly different in approach and characteristics from each other. In this review we describe in detail their mechanisms and applications for the improvement of fruit trees and consider the relationship between these biotechnological tools and the EU biosafety regulations applied to the plants and products obtained through these techniques.